PENGARUH SUHU RUANG PENYIMPANAN TERHADAP KUALITAS SUSU BUBUK - Nelis Immaningsih (AGROINTEK, 2013)
Milk powder is a perishable product that undergoes changes in quality rapidly overtime. This paper studied the effect of temperature on quality of milk powder during storage.Milk powder was stored at 25 and 40ºC, and with or without contact to oxygen by perforatingthe package. Oxygen content, peroxide numbers, wettability, lumps, colour and flecks of milkpowder were examined. Results showed that storage of milk with perforated package at 40ºCresulted in 200 times increase in oxygen content, while that in milk with unperforated packageonly showed 18 times increase in oxygen content. Milk with perforated packaged stored at 25ºChad 34 times increase in oxygen content, while that of milk in unbroken package was only 5times increase. Wettability was increased during storage, but there was no considerabledifference between that in milk broken and unbroken package. At 40°C, wettability of milk wasincreased by 3.4 times in broken package, and 3.11 times in unbroken package. Whilst, at 25ºC,wettability of milk powder was increased by 1.5 times in broken package, but only 0.2 times inunbroken package. There was no significant (P0.05) change in peroxide number over time,and consequently, there was no effect on milk with or without access to atmospheric oxygen.However, highest peroxide numbers was detected in milk kept in broken package at 40ºC. Therewas no detectable change in lumps, colour, and fleck in all treatments.